Impact of a Stretching Program on Musculoskeletal Discomfort in Online Motorcycle Taxi Drivers: A Pre-Post Intervention Study - Hutabarat, Julianus (International Journal of Integrated Engineering, 2024)
The prevalence of musculoskeletal discomfort is a current issue for online motorcycle taxi drivers. Any work must cause muscle complaints. Therefore, this article will answer the problem regarding the impact of musculoskeletal discomfort before and after the stretching program. Statistical tests are needed, including chi-square and Wilcoxon and brainstorming the specifications of the stretching program movement to 70 respondents. It was stated that there was a relationship between the NBM instrument and the respondent’s characteristics and the level of significant differences before and after the stretching program with the specification of 8 stretching movements that could be carried out at 10.00 WIB and 15.00 WIB with an estimated time of up to 24 minutes. It is hoped that this can be a development in reducing musculoskeletal discomfort complaints that are sustainable.